+0  
 
0
131
3
avatar+1227 

Portia solved the quadratic equation \(x^2+(2\sqrt3)x+1=0\)  by completing the square. In the process, she came up with the equivalent equation \((x+r)^2 = s,\) where \(r\) \(s\) and  are constants.

What is \(s\)?

tertre  Mar 11, 2017

Best Answer 

 #2
avatar+79881 
+5

x^2 + 2sqrt(3)x + 1  = 0

 

x^2 + 2sqrt(3)x  = - 1         

 

Take (1/2) of 2sqrt(3)  = sqrt(3)....square this = 3   add to both sides

 

x^2 + 2sqrt(3)x + 3 =  -1 + 3      simpify and factor

 

(x  + sqrt(3) )^2   =    2

 

r =  sqrt(3), s = 2

 

 

 

cool cool cool

CPhill  Mar 11, 2017
Sort: 

3+0 Answers

 #1
avatar+1227 
0

Where is says " r s and are constants", it's actually " r and s are constants

tertre  Mar 11, 2017
 #2
avatar+79881 
+5
Best Answer

x^2 + 2sqrt(3)x + 1  = 0

 

x^2 + 2sqrt(3)x  = - 1         

 

Take (1/2) of 2sqrt(3)  = sqrt(3)....square this = 3   add to both sides

 

x^2 + 2sqrt(3)x + 3 =  -1 + 3      simpify and factor

 

(x  + sqrt(3) )^2   =    2

 

r =  sqrt(3), s = 2

 

 

 

cool cool cool

CPhill  Mar 11, 2017
 #3
avatar+1227 
+5

Thanks so much!

tertre  Mar 11, 2017

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details